Oral & Maxillofacial Imaging Techniques - Rawlani, S. M Shivlal M (Jaypee Brothers Medical Publishers, 2014)
The featured book provides full range of imaging techniques widely used in oral and maxillofacial diagnosis. These techniques are evaluated to get accurate diagnosis radiography which results in outcome of significant image with clear description. Book provides brief introduction and discusses the limitations associated with conventional techniques and compiled all the relevant intellectual benefits of imaging techniques. Each chapter is divided into different radio imaging techniques such as Arthroscopy, Implant Radiology, Tomography, and Magnetic Resonance Imaging which envisions in-depth knowledge and gives complete illustrations by highlighting the procedures, advantages, disadvantages and limitations of it. The presented book also accounts for recent advances in the imaging techniques with inventions of Doppler US, US Biomicroscopy, Elastography, Hybrid arrays and alternative modalities like xeroradiography and scintigraphy practiced in oral and maxillofacial radiodiagnosis. Overall the book forms an excellent reference for researchers, students and medical communities especially in diagnostic centers and dental care.